Romero, Raúl R. Andean and Tropical. The Peruvian cumbia in the global city. Lima: Pontificia Universidad Católica del Perú, Instituto de Etnomusicología Andina, 2008, 104 pp. - Huerta-Mercado, Alexander (2008)
The review does not present a summary